Analytical performance analysis of the M2M wireless link with an antenna selection system over interference limited dissimilar composite fading environments - Došić, Danijel; Milić, Dejan; Kontrec, Nataša; Stefanović, Časlav; Milosavljević, Srdan; Stefanović, Dušan M. (Zielona Góra: Uniwersytet Zielonogórski)
This paper considers direct mobile-to-mobile (M2M) communications with a dual antenna selection (AS) system at a destination mobile node (DMN) in interference limited, dissimilar composite fading environments. In particular, we model dissimilar interference limited signals at the inputs of the dual branch AS system as (i) the ratio of two Nakagami-m (N) random variables (RVs) at the first branch and (ii) the ratio of two Rice RVs at the second branch, in order to account for non line-of-sight (NLOS) and line-of-sight (LOS) communications, respectively.
Keywords: mobile-to-mobile communication; vehicle-to-vehicle communication; Nakagami-m fading; Rice fading; probability density functions; cumulative density functions